If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3x+4=3/2x=3
We move all terms to the left:
1/3x+4-(3/2x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 2x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
1/3x-(+3/2x)+4=0
We get rid of parentheses
1/3x-3/2x+4=0
We calculate fractions
2x/6x^2+(-9x)/6x^2+4=0
We multiply all the terms by the denominator
2x+(-9x)+4*6x^2=0
Wy multiply elements
24x^2+2x+(-9x)=0
We get rid of parentheses
24x^2+2x-9x=0
We add all the numbers together, and all the variables
24x^2-7x=0
a = 24; b = -7; c = 0;
Δ = b2-4ac
Δ = -72-4·24·0
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{49}=7$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-7}{2*24}=\frac{0}{48} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+7}{2*24}=\frac{14}{48} =7/24 $
| 42.7=(.25x)+(.20x)+(.20x) | | A-8/2=4a+10 | | 6x+(1.5x^-4)=-4 | | 6x+1.5x^-4=-4 | | 1x-1=9x+3 | | A=10(h) | | 2+w-3=2w-7 | | A=10x3 | | A=10x3.5 | | x(x-4)+(x-4)=0 | | 1080/x=720 | | (4x+2)^2=196 | | (4x+2)²=196 | | -20(5+2x)=-10-4(-15x-40) | | (x^2-3)(x^2-3)=13 | | 3+y-2+y+7=0 | | -2(3x)+6=4(x-6) | | -2(3x)+6=4*(x-6 | | F(d)=2d | | 20+2x=10x | | (4x+2)=196 | | 4x=27x-(10/5) | | ½(h-6)=0 | | 16/p+9p-5/p+3=9 | | 15–3y=y+13+y | | 10w-5/4=9w+7/4 | | 10w−54=9w+74 | | 3p+(16-p)=28 | | 6z+8=5z+6 | | 2m^2+2m-8=4 | | (-3/5)u=-15 | | 4(8x+2)=8 |